THE EFFECT OF JOB BURNOUT ON ACADEMIC PROCRASTINATION ON WORKING STUDENT - Kamaratih, Dewi; Malada, Eka (Jurnal Ekonomi dan Manajemen, 2022)
This study aims to test the effect of job burnout and academic procrastination on working students. This study uses a sample with a probability sampling technique, which uses students who undergo lectures while working. The number of student populations who took the known night class lecture was 127 students who were then counted using the Slovin formula to get the number of samples of 96 subjects. Data collection techniques in this study use a scale which is then analyzed using simple linear regression analysis. Hypothesis testing in this study shows the result that there is an influence between burnout jobs on academic procrastination in working students. This is indicated by the correlation coefficient number between burnout jobs and academic procrastination is Rxy = 0.341 with a significance value of 0.001 (sig < 0.05) which means there is an influence between burnout jobs on academic procrastination in working students. The higher the burnout job in students, the higher the academic procrastination, and vice versa.